Digital Adolescent Sexual and Reproductive Health in Low- and Middle-Income Countries: A Scoping Review - Russell Dowling; Embry M. Howell; Mark Anthony Dasco; Jason Schwartzman (Youth)
Every adolescent should have the right to make their own choices about their sexual and reproductive health (SRH). Achieving this goal can be challenging, especially in low- and middle-income countries (LMICs), where social norms and insufficient resources may limit access to information. Technology is increasingly being leveraged in LMICs to reach adolescents. We searched the literature to understand the landscape of digital SRH interventions in LMICs. The review addressed three questions: (1) What are the interventions and how effective are they? (2) What are adolescent preferences for information? And (3) What do the interventions cost? There is a wide variety in the populations addressed (e.g., adolescents with HIV, pregnant/post-partum adolescents) and the locations of the interventions, with the majority in sub-Saharan Africa. The types of interventions were evenly distributed between “push” approaches, where adolescents are sent information; “pull” approaches, where adolescents reach information from a website or app; and “two-way” approaches, which combine push and pull aspects. The most positive features identified were convenience and privacy. The major challenge is inadequate smartphone penetration in very low-income adolescents, especially girls. The evidence on the effectiveness of these interventions is mixed. Most studies show that SRH knowledge increases, but this does not necessarily lead to behavior change.